13: FROM OUTSIDERS TO INSIDERS: GRADUATE ASSISTANT DEVELOPMENT AT STATE COMPREHENSIVE UNIVERSITIES. (10th October 2017) - Brennan, Kathleen M.; Cruz, Laura; Kinner, Freya B.
Abstract : We assess graduate assistant competency in key skills that employers in and outside of academia value and examine whether these skills are developed in the context of the graduate assistantship (GA) at a specific state comprehensive university. The GAs in our sample rate themselves as competent or very competent on all skills and report their GA experience somewhat influenced or influenced their skill competencies. Furthermore, perception of how one's graduate assistantship influenced skill competency was significantly associated with perceived skill competency level. Based on these findings, we discuss distinct gaps that could be addressed to facilitate GA development at state comprehensive universities.